Biostimulants for sustainable development of agriculture: a bibliometric content analysis - Dinesh Chand Meena; Pratap Singh Birthal; T. M. Kiran Kumara (Discover Agriculture)
Abstract This paper presents a bibliometric content analysis of the research on biostimulants to examine their roles in improving the sustainability of agriculture. The research on biostimulants is developing and has been attracting significant attention. It has focused on understanding the functional mechanisms of biostimulants and their impact on various indicators of sustainability. It suggests that biostimulants improve crop yield and product quality, reduce external application of fertilizers, enhance water-use efficiency, and improve crops’ capability to tolerate abiotic stresses. Given the growing negative externalities of intensive agriculture to natural resources, human health, and the environment and the predictions of climate becoming more severe, there is a need to focus more on basic and applied research on biostimulants.